A PILOT STUDY on the Clinical and Functional Outcomes of an Improvised Technique of Core-cut Fistulectomy for Fistula-in-ano. (June 2022) - Parwez, Masoom; Huda, Tanweerul; Yadav, Moorat S.; Gupta, Kamal; Mital, Kushal; Pandya, Bharati
Background: Anal fistulae are difficult to treat entities and minimally invasive procedures are evolving with promises. Our improvised technique is a simple and easy day-care procedure for simple fistulae. Aim: To evaluate the outcomes of a technical modification in the procedure of core-cut fistulectomy in simple cryptoglandular fistula-in-ano. Methods: 47 patients of fistula-in-ano presenting to the out-patient of the General Surgery department at All India Institute of Medical Sciences, Bhopal, from November 2018 to March 2020 were selected. A complete history, physical examination followed by relevant investigations were meticulously performed and recorded. They were operated using an improvised core-cut technique, under a pudendal nerve block. Patients were kept on follow-up for a minimum of 6 months period to note the outcome of the surgery. Results: The mean age was 37 ± 13.17 years with a male: female ratio of 5.1:1. The most common clinical presentation was perianal discharge in 96% of patients followed by pain and pruritus ani in 45% and 32%, respectively. 93.62% were inter-sphincteric, and 6.38% were trans-sphincteric. Extra-sphincteric and supra-levator fistulae were excluded from the study. The mean operative time was 17 ± 10.19 minutes. The mean healing time was 19.21 ± 5.99 days. The success rate of this novel technique of core-cut was calculated to be 89.37%. The rate of recurrence was calculated to be 10.63% (5 out of 47 patients). None of our patients developed incontinence. Conclusion: Our pilot study results for simple fistulae-in-ano had less morbidity, postoperative pain, better wound healing, patient satisfaction, and compliance with low risk of recurrence, and no incontinence. It could hence be recommended for larger groups and more complicated fistulae in the future.